Analysis of Reservoir Seismic Law Based on Three-Dimensional Morphological Characteristics of Joint Surface Related to Listric Fault - Duan, Guoyong; Wang, Yanhai; Chen, Jianghong; Zhang, Jingyu (Frontiers in Physics, 2022)
Since water storage, earthquakes occurred in Badong County, Hubei Province, accounted for as much as one-third of the strong earthquakes in the Three Gorges Reservoir area. For example, the MS5.1 earthquake occurred in December 2013 near the Gaoqiao fault in Badong County. The earthquake time, magnitude, and location analysis showed that reservoir earthquakes in this area exhibited some characteristics, such as periodicity, migration, and deep extension. Based on the regional stratum lithology and structural characteristics, this paper designed a curved joint on a small scale to simulate the structural morphology of the Gaoqiao fault and carried out triaxial compression tests under different immersion times to analyze the morphological parameters of the joint surface. The results showed that topological parameters such as root mean square height (Sq), arithmetic average height (Sa), reverse load area ratio (Smc), and minimum autocorrelation length (Sal) could effectively characterize the degree of damage and deterioration of curved joints. The test privides a reference for analyzing the evolution law of the seismic characteristics of the reservoir.